2009
DOI: 10.1073/pnas.0909015107
|View full text |Cite
|
Sign up to set email alerts
|

NeuroD1 induces terminal neuronal differentiation in olfactory neurogenesis

Abstract: After their generation and specification in periventricular regions, neuronal precursors maintain an immature and migratory state until their arrival in the respective target structures. Only here are terminal differentiation and synaptic integration induced. Although the molecular control of neuronal specification has started to be elucidated, little is known about the factors that control the latest maturation steps. We aimed at identifying factors that induce terminal differentiation during postnatal and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 36 publications
6
122
0
1
Order By: Relevance
“…Our data suggest that similar events take place on the Prox1 enhancer region, given the repression of SOX9 on β-catenin-induced activation in luciferase reporter constructs containing parts of the Prox1 enhancer region. Notably, NeuroD1 is also required for the generation of certain olfactory neurons (11,13,14). Thus, the data presented here add an important piece to the transcriptional mechanisms What could be the downstream targets of Prox1 that are important for neuronal differentiation in vitro and in vivo?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that similar events take place on the Prox1 enhancer region, given the repression of SOX9 on β-catenin-induced activation in luciferase reporter constructs containing parts of the Prox1 enhancer region. Notably, NeuroD1 is also required for the generation of certain olfactory neurons (11,13,14). Thus, the data presented here add an important piece to the transcriptional mechanisms What could be the downstream targets of Prox1 that are important for neuronal differentiation in vitro and in vivo?…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that NeuroD1, a basic helix-loop-helix transcription factor required for granule cell genesis in the embryonic and adult DG, is regulated by β-catenin-dependent signaling (9)(10)(11)(12). However, NeuroD1 is not only important for hippocampal neurogenesis but is also involved in the generation of SVZ-derived olfactory neurons (11,13,14). Thus, the network of genes regulated by the Wnt pathway to selectively generate DG granule cells in the adult hippocampus remains unknown.…”
mentioning
confidence: 99%
“…20,21 NEUROD1 has been shown to play critical roles in multiple biological processes including endocrine cell development, neurogenesis, and glucose homeostasis. [22][23][24][25][26] Several reports associate NEUROD1 mutations with human genetic disease, though almost all of these reports have focused on diabetes. Heterozygous LOF mutations in NEUROD1 can cause autosomal dominant type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…2B). NEUROD1, a basichelix-loop-helix (bHLH) transcription factor normally implicated in the regulation of later stages of neuronal differentiation, including terminal neuronal differentiation in olfactory neurogenesis, [47][48][49][50] showed substantial expression at d12 (Fig. 2A).…”
Section: Dnmt3b Does Not Affect Early Ne Specification In Hescsmentioning
confidence: 99%